1969
DOI: 10.3758/bf03212795
|View full text |Cite
|
Sign up to set email alerts
|

Perceived movement of the afterimage during eye movements

Abstract: "When the eyes move, the after-image moves in the same way [Helmholtz, 1924]." Since Helmholtz, if not before, it has generally been assumed that an afterimage would appear to move if the eyes were moving while it was viewed. The general basis of this notion is the phenomenon of position constancy: the fact that despite movements of the 0 that cause the image to move over the retina, a stationary scene will continue to look stationary. It is plausible to believe that position constancy is the result of a proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
1

Year Published

1970
1970
1992
1992

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(19 citation statements)
references
References 4 publications
2
16
1
Order By: Relevance
“…If this were the case, then, since no retinal displacements would be registered during an eye movement, there would be no reason to expect a loss of position constancy during eye movements, and there would be no reason to postulate some kind of comparator that could match retinal displacement to 0 movement information. That this cannot be the case may be seen from the fact that there is evidence that an afterimage appears to move even when it is viewed in complete darkness and the only 0 movement is 0 eye movement (Mack & Bachant, 1969). This suggests that at least the absence of any retinal displacement during an eye movement constitutes a baSis for movement perception.…”
Section: New School For Social Researchmentioning
confidence: 77%
“…If this were the case, then, since no retinal displacements would be registered during an eye movement, there would be no reason to expect a loss of position constancy during eye movements, and there would be no reason to postulate some kind of comparator that could match retinal displacement to 0 movement information. That this cannot be the case may be seen from the fact that there is evidence that an afterimage appears to move even when it is viewed in complete darkness and the only 0 movement is 0 eye movement (Mack & Bachant, 1969). This suggests that at least the absence of any retinal displacement during an eye movement constitutes a baSis for movement perception.…”
Section: New School For Social Researchmentioning
confidence: 77%
“…This assumption is made explicitly by Koffka (1935). Bruell and Albee (1955), Walls (1951), Rock and Ebenholtz (1962), Gregory (1958), and Mack and Bachant (1969), and implicitly by many others. It has long been known (Dodge, 1906), however, that the pursuit is a distinctly different eye movement from the saccade, and recently gathered evidence (Rashbass, 1967) indicates that different brain centers may be involved in the control of each type of eye movement.…”
mentioning
confidence: 97%
“…Almost all theories (Helmholtz 1866; Hering, 1879; James, 1890;Sherrington, 1918;Koffka, 1935;Bruell & Albee, 1955;Walls, 1951;von Holst, 1954;Rock & Ebenholtz, 1962;Mack & BacHant, 1969) seem' to agree that image motion produced by saccadic eye movemen ts somehow is cancelled by the taking-into·account process. 2 These theories will be referred to here as cancellation theories.…”
mentioning
confidence: 99%
“…Thus, the wrist of the right hand was already hyperextended toward the right when the rod was gripped without any slant, giving an attenuated range of wrist motion in this direction (in response to leftward stimulation), compared with the range available for leftward wrist rotation (in response to rightward stimulation). Other studies in which the plane of rod rotation was normal to a frontal plane have found no effect of stimulus direction (Heck- curring with afterimages and imaginary targets is consistent with this identity, since pursuit itself is similarly effective with afterimages (Mack & Bachant, 1969) and during imaginary and predicted target motions (Steinbach, 1976;Whittaker & Eaholtz, 1982). A predictive component of nystagmus suppression has also been detected (Larsby, Hyden, & Odqvist, 1984).…”
Section: Resultsmentioning
confidence: 80%